An assessment of bovine herpes virus 4 as a causative agent in abortions and neonatal death - Dağalp, Seval B. (Onderstepoort J Vet Res, 2020)
Numerous viruses, including bovine viral diarrhoea virus (BVDV), bovine herpes virus 1 (BoHV-1) and bovine herpes virus 4 (BoHV-4), and other pathogens are the most common causes of reproductive disorders and are responsible for huge economic losses in livestock production. This study investigates the aetiological role of BoHV-4 in fertility problems such as abortions, stillbirth and birth with unviable calves. Retrospective samples from 38 animals, including 17 aborting cows, 17 aborted foetuses, three stillborn calves and one unviable newborn calf were analysed. The BoHV-4 genome was detected in 25 (65.7%) animals by polymerase chain reaction. In 14 of these infected animals, we detected co-infection with BVDV, while the co-presence of BoHV-1 was also detected in one animal. In addition to the high prevalence of BoHV-4 genome in materials related to fertility problems, isolation of BoHV-4 from the brain of one stillborn calf indicated a causal link between BoHV-4 and fertility problems, such as abortion, stillbirths or birth with unviable calves.